MODERN APPROACHES TO DESIGNING A SAFE ENVIRONMENT IN GENERAL SECONDARY EDUCATIONAL INSTITUTIONS - Shvardak, Marianna; Popovych, Oksana (Continuing Professional Education: Theory and Practice, 2025)
The article considers the problem of designing a safe educational environment in the context of modern challenges caused by social transformations, the COVID-19 pandemic, war, as well as the rapid development of digitalization, which, despite its numerous advantages, creates new challenges in the field of educational security. The purpose of the study is to substantiate and analyze technological, social, inclusive, and organizational and managerial approaches to designing a safe educational environment in the context of modern challenges. The methodological basis is a set of approaches (systemic, synergistic, axiological), which provides a systematic understanding of the problem of a safe educational environment. A review of the latest scientific publications covering the problems of security in education in the context of digitalization, social transformations, pandemics, and military threats is carried out. The article identifies and characterizes four key approaches to designing a safe environment. The technological approach involves the use of digital tools: video surveillance systems, smart locks, online psychological assistance platforms and mobile applications for teaching safe behavior. The social approach includes the development of mediation programs, the formation of emotional intelligence skills and a culture of non-violent communication. The inclusive approach is aimed at creating a barrier-free environment and adapting educational programs for children with special needs. The organizational and managerial approach includes the implementation of zero-tolerance policies for violence, the creation of school safety teams, and the training of personnel for actions in crisis situations. It is summarized that ensuring a safe educational environment requires the systematic implementation of innovations aimed at increasing the resilience of education to modern threats. Based on the analysis of modern practices, it was established that the comprehensive implementation of modern approaches contributes to strengthening safety in education.